329 Efficacy and Safety of Riluzole in Acute Spinal Cord Injury: Rationale and Design of AOSpine Phase III Multicenter Double-Blinded Randomized Controlled Trial (RISCIS). (August 2016) - Fehlings, Michael G.; Kopjar, Branko; Grossman, Robert G.
Abstract : INTRODUCTION: There is convincing evidence from the preclinical realm that the pharmacologic agent riluzole attenuates certain aspects of the secondary injury cascade leading to diminished neurological tissue destruction in animal spinal cord injury (SCI) models. The safety and pharmacokinetic profile of riluzole have been studied in a multicenter pilot study in 36 patients. Efficacy of riluzole in acute human SCI has not been established. METHODS: This ongoing multi-center, international double-blinded phase III randomized controlled trial will enroll 351 patients with acute C4 C8 SCI and ASIA Impairment Grade A, B, or C randomly assigned 1:1 to riluzole and placebo. Primary outcome is the change in ASIA Motor Score (AMS) between baseline and 180 days. Other outcomes include ASIA Upper and Lower Extremity MS; ASIA Sensory Score; ASIA grade; SCIM; SF-36v2; EQ-5D and GRASSP. Two-stage sequential adaptive trial statistical design has 90% power to detect 9 points difference in the ASIA Motor Score at 1-sided α = 0.025. RESULTS: A matched cohort analysis performed in the phase I study showed that riluzole-treated cervical SCI patients experienced an additional 15.5 points in AMS recovery at 90 days postinjury. Although the phase I study was underpowered to investigate efficacy, the current phase III study is poised to definitively address this question. Subject enrollment for this trial began on October 1, 2013 in 11 international centers. To date, 40 subjects have been enrolled. Average age of the enrolled subjects is 48.4 (SD 16.4); 80% males. ASIA at arrival and Pre-Injury status, ASIA Grade A (46%), B (26%), C (29%). GRASSP 66.2 (SD 74.6), SF35v2 PCS 52.9 (SD 8.8) SF36v2 MCS 55.8 (SD 12.3). CONCLUSION: This is a phase III study of riluzole in acute SCI.